Towards Better Understanding of the Pathogenesis of Neuronal Respiratory Network in Sudden Perinatal Death - Mehboob, Riffat; Kabir, Mahvish; Ahmed, Naseer; Ahmad, Fridoon Jawad (Frontiers in Neurology, 2017)
Sudden perinatal death that includes the victims of sudden infant death syndrome, sudden intrauterine death syndrome, and stillbirth are heartbreaking events in the life of parents. Most of the studies about sudden perinatal death were reported from Italy, highlighting two main etiological factors: prone sleeping position and smoking. Other probable contributory factors are prematurity, male gender, lack of breastfeeding, respiratory tract infections, use of pacifiers, infant botulism, extensive use of pesticides and insecticides, etc. However, extensive studies across the world are required to establish the role of these factors in a different subset of populations. Previous studies confirmed the widely accepted hypothesis that neuropathology of the brainstem is one of the main cause of sudden perinatal death. This study is an effort to summarize the neuropathological evaluation of the brainstems and their association to sudden perinatal death. Brainstem nuclei in vulnerable infants undergo certain changes that may alter the sleep arousal cycle, cardiorespiratory control, and ultimately culminate in death. This review focuses on the roles of different brainstem nuclei, their pathologies, and the established facts in this regard in terms of it’s link to such deaths. This study will also help to understand the role of brainstem nuclei in controlling the cardiorespiratory cycles in sudden perinatal death and may provide a better understanding to resolve the mystery of these deaths in future. It is also found that a global initiative to deal with perinatal death is required to facilitate the diagnosis and prevention in developed and as well as developing countries.